PENGARUH PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN ( KASUS KARYAWAN PT. PERAWANG KENCANA MOTOR) - Angraeni, Ike; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Supervision of the company is carried out effectively by a leader who in this case is a manager, because the supervision of an employee getting the attention, guidance, instructions and directives from his superiors so that the company hopes its own employees to provide the best to the company where she worked ,This study aims to determine the effect of work monitoring the performance of employees of PT. Perawang Kencana Motor. Data were obtained from questionnaires with respondents as many as 39 people processed further by statistical methods descriptive and then the data is presented in fomrmat tables and figures and percentages for the results of the analysis further showed that supervision has a good influence on the performance of employees at PT. Perawang Kencana Motor. Employee performance is influenced by supervisory work to the value of R Square of 0.799. This means that the contribution of labor supervision variable influence to variable employee performance is 79.9% while the remaining 20.1% is influenced by other variables not included in this regression model.Keywords: supervision of work, employee performance